Analysis of Numeracy Ability in 4th grade Students at SDN 128 Haurpancuh Bandung - Putri, Santika; Suryadi, Didi (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2024)
The culture of numeracy in Indonesia is low. The factor that influences the low numeracy in Indonesia is the lack of interest in reading among Indonesian people. Numerasi itself can be linked to skills in certain fields. This research uses descriptive qualitative research. The aim of this research is to analyze the numeracy abilities of 4th grade students. The subjects of this research involved 26 4th grade students at SDN 128 Haurpancuh. The research instruments were used in this research is interview sheets and student evaluation sheets in the form of number pattern questions to analyze students' numeracy abilities. Based on the results of research from 26 students who worked on worksheets in the form of number pattern questions, there were 5 students who had low level numeracy abilities, 9 people had medium level numeracy abilities, and 11 students had high level numeracy abilities. So it can be concluded that the numeracy literacy skills of 4th grade students at SDN 128 Haurpancuh are at a medium level.